Association analysis of ESR gene polymorphism and carcass traits in egg quails (Coturnix coturnix) - BAI, JUN YAN; DONG, ZHI HAO; LU, XIAO NING; HUANG, ZHI YANG; LI, ZI HENG; GONG, HUI RONG; HU, QI HANG; HUANG, GAO XIANG; FAN, ZHENG YU (The Indian Journal of Animal Sciences, 2021)
The polymorphism of estrogen receptor (ESR) gene was detected by PCR-RFLP in China yellow, Korean and Beijing white quails and the association between ESR gene polymorphism and carcass traits of egg quails was analyzed. The results showed that there were three genotypes including CC, CT and TT detected in exon 1 and exon 8 of ESR gene in egg quails. The frequencies of CC genotype in exon 1 of ESR gene were the highest in China yellow, Beijing white and Korean quail (0.515, 0.614, 0.723). The highest frequencies of TT genotype in exon 8 of ESR gene were detected in Beijing white and Korean quails (0.618 and 0.540), while the highest frequency of CT genotype was detected in China yellow quail (0.476). As demonstrated in this study, there were significant correlations between exon 1 of ESR gene and body weight, carcass weight, breast muscle weight, heart weight and percentage of leg muscles in egg quails (P